2009
DOI: 10.1021/la9015146
|View full text |Cite
|
Sign up to set email alerts
|

Metal−Polymer Hybrid Colloidal Particles with an Eccentric Structure

Abstract: We have synthesized metal-polymer hybrid colloidal particles characterized by an eccentric structure by precipitation polymerization in the presence of metal colloids. The key to the formation of an eccentric core-shell structure was to introduce metal colloids a few minutes after (rather than before) starting the polymerization. The hybrid particles were uniform in size, and each one of them contained only one metal nanoparticle at its surface after the experimental procedures had been optimized. This method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…It is possible that the physically bound stabilizers (CTAB and citrate) could be displaced by ligands that could bind to the Au nanostructures more strongly. [11c,14] The surface charges of citrate-stabilized nanospheres were not changed substantially upon suspension in the culture medium; this might be mainly due to the displacement of citrate by similarly-charged proteins. [15] Chithrani et al also suggested that the citrate-stabilized Au nanospheres could be modified by serum proteins, which could induce the uptake of the Au nanospheres by cells via receptor-mediated endocytosis.…”
mentioning
confidence: 99%
“…It is possible that the physically bound stabilizers (CTAB and citrate) could be displaced by ligands that could bind to the Au nanostructures more strongly. [11c,14] The surface charges of citrate-stabilized nanospheres were not changed substantially upon suspension in the culture medium; this might be mainly due to the displacement of citrate by similarly-charged proteins. [15] Chithrani et al also suggested that the citrate-stabilized Au nanospheres could be modified by serum proteins, which could induce the uptake of the Au nanospheres by cells via receptor-mediated endocytosis.…”
mentioning
confidence: 99%
“…[10c, 11] Herein, we report an ew method for the facile encapsulation of fatty acids in biocompatible,s ilica-based nanocapsules with aw ell-defined hole in the wall for the temperature-controlled release of therapeutics.T he nanocapsules are prepared through site-selected deposition by templating with Au-PS Janus colloidal particles.T heir wall can be designed to contain aw ell-defined hole for easy loading and controlled release.Amixture of lauric acid and stearic acid with ae utectic melting temperature at 39 8 8Cc an be readily loaded into the nanocapsule through the hole,t ogether with at herapeutic agent and an ear-infrared (NIR) dye.U pon irradiation with aN IR laser (or through direct heating), the fatty acids will be melted to trigger the release of the payloads.T he amount of the released drug can be controlled by varying the size of the hole and/or the duration of laser irradiation. [15] TheA u-PS particles had au niform diameter of 176 AE 4nm, in which the 50-nm Au nanoparticles (Figure S1 A) were partially embedded in the PS beads.A fter the hydrolysis of vinyltrimethoxysilane (VTMS) in the presence of ammonia, at hin shell of vinylsilica was formed only on the PS region, generating aparticle whose surface was incompletely coated by vinyl-silica . Thes ilica nanocapsules can also be readily modified with functional groups such as targeting moieties.…”
Section: Encapsulation Of Ap Hase-change Materials In Nanocapsules Witmentioning
confidence: 99%
“…They demonstrated that controlling synthetic conditions could change the core size and the silica shell thickness. Ohnuma et al trapped single Au or Ag nanoparticles in polymer particles [8,9]. In addition, Fayen et al produced so-called mushroom nanostructures by trapping single Fe 2 O 3 nanoparticles in silica shells [10].…”
Section: Introductionmentioning
confidence: 99%